PENGENALAN TEKNOLOGI OLAHAN PERIKANAN KEPADA SISWA SD NEGERI 2 TABONGO - A. Dali, Faiza (Merwinspy Publisher, 2025)
This activity aims to introduce simple technologies in fish processing, including the production of smoked fish, canned fish, fish floss, and fish crackers, as well as to provide students with an understanding of the benefits of fish and its processing technologies as a form of education in the field of processed fishery resources. The methods used include interactive lectures, video screenings about the fish processing process, and tests given to students to assess their level of understanding. The results of this activity show a significant increase in students' knowledge, especially in recognizing the nutritional benefits of fish and its processing methods. Based on the pre-test and post-test, there was an increase in students' understanding of over 50% on the topic of fish processing technology. The edutainment approach implemented successfully built students' enthusiasm and motivation to learn, as evidenced by their active participation during the activities. The awarding of prizes to outstanding students also supports their interest in studying this topic. This activity is expected to be a first step in introducing students to a deep understanding of the beneficial and sustainable processing of local resources from an early age.